A comprehensive examination of women in terrorism - Caffera, Catherine Elizabeth Antes (Kansas State University, 2019)
Women are a growing and deadly presence in terrorism; however, existing literature has found that female terrorists are often misunderstood and underestimated as a security threat. Furthermore, existing counterterrorism measures appear to have little effect on female terrorists in particular. There is clear need for a greater understanding of women in terrorism. Most analyses of women in terrorism are qualitative and small-scale, though, and there is little large-scale statistical data on women in terrorism in the extant literature. The relative lack of understanding of women in terrorism represents an important gap in the literature. This thesis presents a unified theory of the entire arc of women’s experiences in terrorism, from their choice to participate in politically-motivated violence to the challenges they face when attempting to leave and reintegrate into society. I argue that the decision to join terrorist groups is often gendered for women, and the gendered aspect of women in terrorism accounts for many of the disparate findings in terrorism literature. I conduct a global regression analysis on the effects of several gendered variables on instances of suicide terrorism. I find that while the impact of women’s access to employment and the number of women in the national parliament is not significant, the gender parity of access to education is highly correlated with instances of suicide terrorism in general, and among women. Fertility rate has a complex relationship with women’s likelihood to engage in suicide terrorism Furthermore, instances of suicide terrorism in society in general increase the likelihood that women will engage in suicide terrorism in a given country. I also analyze the literature on Disarmament, Demobilization, and Reintegration programs and post-conflict program analyses, and their impact on women. I find that such programs often systematically exclude or fail women, and that these programs generally do not include the kind of aid that is most important to female ex-combatants, and which represent the greatest barriers to their reintegration. I argue that significant policy changes are necessary to truly meet the needs of female ex-combatants and terrorists, and to create a safer and more positive post-conflict environment.
Keywords: Terrorism; Gender; Women; DDR; Combatant; Terrorist